1993
DOI: 10.1042/bj2900199
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of glutathione S-transferases from rat olfactory epithelium

Abstract: The glutathione S-transferases (GSTs) of rat olfactory epithelium have been characterized with regard to substrate specificity and subunit composition and compared to those of the liver. The presence of cytosolic GST activity in rat olfactory epithelium was confirmed and, using 1-chloro-2,4-dinitrobenzene as substrate, was found to be approximately one-third that of the liver. Olfactory microsomal GST activity was greater than that of liver microsomes and could be activated by treatment with the sulphydryl age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The occurrence of six different GST isoenzymes able to metabolise several odorant molecules has been demonstrated in this tissue (Ben-Arie et al, 1993;Banger et al, 1993). As is the case for EH, both soluble and microsomal GST have been described, and the olfactory microsomal GST displays activities that reach the same levels as the hepatic isoform (Banger et al, 1993).…”
Section: Olfactory Mucosa ‡mentioning
confidence: 96%
See 1 more Smart Citation
“…The occurrence of six different GST isoenzymes able to metabolise several odorant molecules has been demonstrated in this tissue (Ben-Arie et al, 1993;Banger et al, 1993). As is the case for EH, both soluble and microsomal GST have been described, and the olfactory microsomal GST displays activities that reach the same levels as the hepatic isoform (Banger et al, 1993).…”
Section: Olfactory Mucosa ‡mentioning
confidence: 96%
“…As is the case for EH, both soluble and microsomal GST have been described, and the olfactory microsomal GST displays activities that reach the same levels as the hepatic isoform (Banger et al, 1993). The physiological role of olfactory GSTs remains unclear, but it has been suggested that they may have a role in olfaction, by rapid cleaning of odorants to maintain acuity of olfaction (Banger et al, 1996).…”
Section: Olfactory Mucosa ‡mentioning
confidence: 96%
“…Based on its biochemical characteristics, cytosolic GST is usually divided into four classes: alpha, mu, pi, and theta (Mannervik and Danielson 1988;Meyer et al 1991). Previous studies have shown high expression of GST protein and/or mRNA in the olfactory epithelium of rats (Banger et al 1993;Ben-Arie et al 1993). Immunoreactivities of GST were localized in the sustentacular cells and Bowman's gland of the olfactory epithelium in adult rats (Banger et al 1994) and rats during development (Krishna et al 1994).…”
Section: Introductionmentioning
confidence: 96%
“…Since several phase I and phase II xenobiotic metabolizing enzymes were already detected in the olfactory epithelium of the mammals, the xenobiotic metabolizing system is considered to play important roles in the chemical homeostasis of the olfactory epithelium [2,4,15]. In particularly, the existences of olfactory specific isoforms were reported in cytochrome P450 as phase I enzyme [17] and UDP-glucuronosyl transferase as phase II enzyme [14] in mammalian olfactory epithelia.…”
mentioning
confidence: 99%